Cinética da eletrodeposição simultânea de ZnCo - Tomachuk, C. (2013)
In order to be adopted by the industrial field, the alloys electrodeposition process must produce electrodeposits with the same composition and properties in as wide as possible electrodeposition parameters region. This implies the need to know not only the metals' electrodeposition kinetics in aqueous electrolytes containing both metals but also how that kinetics is affected by the metals relative concentration.